Effects of trimetazidine on crush injury of the sciatic nerve in rats: A biochemical and stereological study - Serayslan, Yurdal; Bal, Ramazan; Altug, Muhammed Enes; Kontas, Tuenay; Keles, Osman Nuri; Unal, Deniz; Unal, Bunyami (Elsevier, 2009)
Trimetazidine (TMZ) is an anti-ischemic agent which has been used for years as an effective anti-anginal agent in cardiac patients. The aim of the study was to investigate the effect of TMZ on the level of malondialdehyde (MDA), nitric oxide (NO), glutathione (GSH), catalase (CAT), histopathological changes and the number of myelinated axons in a crush injury model of sciatic nerve in rats. In this study, 50 Wistar albino rats were used and the right sciatic nerves of all animals were injured. They were randomly divided into two groups equal in number, called treatment and non-treatment groups. The animals were subdivided into four subgroups, non-injury/non-treatment (left sciatic nerves of non-treatment animals, NI-NT) and non-injury/treatment (left sciatic nerves of treatment animals, NI-T) and injury/non-treatment (right sciatic nerves of non-treatment animals, I-NT) and injury/ treatment (right sciatic nerves of treatment animals, I-T). At the end of the experiment, the bilateral sciatic nerves and blood samples collected from these animals were analyzed using histological, stereological and biochemical methods. There was a progressive increase in the serum level of GSH and progressive decrease in serum MDA levels in the treatment group. Progressive decrease in serum NO levels was observed in the treatment groups and it was statistically significant on day 14 (p<0.05) compared to the non-treatment group. The activities of CAT were low in the treatment groups on days 21 (p < 0.05) and 42 (p < 0.05). In the NI-NT group, some unimportant degenerative changes such as irregularity in myelin sheets were observed. Many pathologic changes in the I-NT group and some minimal degeneration in the I-T group were observed. TMZ treatment resulted in increases in the myelinated axon numbers by a range of 223 to 604 in the I-NT group compared to the I-T. In conclusion, TMZ appears to be beneficial for induction of axonal regeneration and myelination in healthy nerves as well as injured nerves. (C) 2008 Elsevier B.V. All rights reserved.
Keywords: Trimetazidine; Injury; Stereology; Myelin sheath; Nerve injury; Histopathology; Sciatic nerve